Sensorless direct torque control based on seven-level torque hysteresis controller for five-phase IPMSM using a sliding-mode observer - Bıçak, Aykut; Gelen, A. (Elsevier B.V., 2021)
This paper proposes sensorless control of the seven-level torque hysteresis controller (7LTHC) in the direct torque control (DTC) method for five-phase interior permanent magnet synchronous motor (IPMSM). Both torque response and torque ripples of the machine are directly related to the amplitude and location of voltage vectors in the hysteresis DTC method. Additionally, different level torque hysteresis controllers are used to configure a variety of voltage vectors. In this paper, 7LTHC is compared with three-level hysteresis torque controllers (3LTHCs) by using different amplitude voltage vectors to validate the DTC based on the proposed 7LTHC method in Matlab/Simulink environment. Dynamic torque response in the transient operation and low torque ripple and low stator current harmonics in the steady-state operation can be achieved by using the proposed 7LTHC. Furthermore, the speed of IPMSM which is controlled by the DTC based on the proposed 7LTHC is estimated using a sliding-mode observer (SMO) based on sigmoid function and the speed performance is enhanced by combining angle tracking observer (ATO) with the SMO. The simulation results confirm the performance of DTC based on the proposed 7LTHC using the structure of hysteresis DTC and the mathematical model of five-phase IPMSM which uses an SMO for sensorless speed control. © 2021 Karabuk University
Keywords: Direct torque control (DTC); Five-phase interior PMSM; Sliding-mode observer (SMO); Torque ripple; Total harmonic distortion (THD)